SAT0264 Efficacy and Safety of TOCILIZUMAB in Elderly Patients with Rheumatoid Arthritis. (10th June 2014) - Pers, Y.-M.; Schaub, R.; Fortunet, C.; Constant, E.; Lambert, J.; Godfrin-Valnet, M.; Pallot-Prades, B.; Wendling, D.; Gaudin, P.; Marotte, H.; Maillefert, J.-F.; Jorgensen, C.
Abstract : Objectives: To assess safety and efficacy of tocilizumab (TCZ) in elderly (≥65 years) rheumatoid arthritis (RA) patients treated in daily practice. Methods: We conducted a retrospective study of TCZ use in RA patients followed in five French university hospitals from 2009 to 2012. We considered two age groups (<65 and ≥65 years). TCZ efficacy was evaluated at 24 weeks by the European League Against Rheumatism (EULAR) response and remission score. We also evaluated drug maintenance and safety (adverse events discontinuation). A multivariate cumulative logit model for ordinal categories was performed to assess the relationship between age class and EULAR response (none, moderate and good) adjusted on possible confounders. TCZ retention (drug survival) over time was estimated with the Kaplan-Meier method. Treatment retention curves were compared according to age group with the log-rank test. Results: Among 222 RA patients treated by TCZ, 61 (27.5%) were ≥65 years at therapy initiation. After 6 months, elderly patients less often reached remission (27.8% versus 45.6%; p=0.02) or good EULAR response (40.7% versus 61.0%; p<0.01). Multivariate analysis adjusted on baseline C-Reactive protein confirmed that elderly patients were more likely to have a lower EULAR response (none vs. moderate-good or none-moderate vs good) (OR: 3.16; 95%CI [1.68; 5.96], p<0.001). Drug maintenance for TCZ and adverse events discontinuation rates were similar between age groups. Conclusions: In daily practice, TCZ seems well tolerated but less efficient in elderly RA patients. Broader analyses like international register are now needed to confirm our results. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.1513